ACE I/D polymporphism in young runners - Rogozkin, V.; Astratenkova, I.; Komkova, A.; Voroshin, I. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction There is increasing evidence for strong genetic influence on athletic performance. The angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism has previously been associated with measures of training response and human endurance performance. ACE expressed in human skeletal muscle would seem to influence its function. The ACE I allele has been associated with elite endurance performance and the D allele with performance over shorter distances in runners and swimmers (Myerson et al., 1999, Woods et al., 2001). We have previously reported that the I variant was associated with improved endurance performance on Russian athletes (Nazarov et al., 2001). The aim of this study was to examine the hypothesis of an possible association between I/D ACE gene polymorphism and elite runner athletes (ERA) status. Methods We examined the DNA of 33 male ERA (age: 20.7 +/- 2.7 yrs, height: 182.5 +/- 6.1 cm, weight: 74.0 +/- 4.9 kg) and 40 male controls (CON). All runners were grouped by independent experts according to distance run: .200 m (predominantly anaerobic or power), 400 m and 800 m (mixed aerobic and anaerobic). The ACE polymorphism typed by PCR method using three primers and products resolved on a 7.5% polyacrylamide gel. Results We therefore examined genotype distribution of the ACE gene amongst the ERA and CON. There were no significant differences in allelic (ERA: I=47%, D=53% and CON: I=46%, D=54%) and genotypic (ERA: II=21%, ID=52%, DD=27% and CON: II=20%, ID=52%, DD=28%) frequency between groups (Fig.1). Analysis revealed a linear trend of increasing I allele frequency with distance run, when grouped into 200 m, 400 m and 800 m (Table 1). The proportion of I alleles increased from 0.23 to 0.40 and 0.62 amongst running 200 m (n=7), 400 m (n=20) and 800 m (n=6) respectively. Discussion/Conclusion These results support the hypothesis that the insertion (I) allele of the ACE gene may be associated with improved skeletal muscle endurance in response to training and such an effect might influence general sporting prowess. Those findings suggest that DNA sequence variation in ACE gene is part of the complex genotype associated with elite runner status. The results indicated of great importance of genetic analysis in selecting young athletes to entering a professional sport. The result is that there are genetic differences among individuals such as we have demonstrated for the ACE locus, that may be useful predictions of athletic performance at the elite level. It will be an able to improve the efficiency training of athletes.